Perbandingan Informasi Anatomi Pemeriksaan Articulatio Genu AP Weight Bearing dan AP Supine pada Kasus Osteoarthritis di Instalasi Radiologi - Hasbi, Nurul Auliyaa; Rusli, Muh; Jamal, Nurul Jannah (Poltekkes Kemenkes Semarang, 2026)
Background: The articulatio genu is a complex joint formed by the femur, tibia, and patella. Radiographic examination is important for evaluating anatomical changes in osteoarthritis. Different radiographic positions, such as anteroposterior (AP) weight-bearing and AP supine projections, may provide different anatomical information. Methods: This quantitative study was conducted at Dr. Tadjuddin Chalid General Hospital, Makassar. Data were collected through observation guidelines and questionnaires. The sample consisted of four patients, and data were analyzed using the Friedman test with SPSS. Results: The Friedman test showed that the mean rank of the AP weight-bearing projection was 3.60, which was higher than the mean rank of the AP supine projection (3.47) with p value = 0,000. Conclusions: The AP weight-bearing projection provides more optimal and clearer anatomical information than the AP supine projection in articulatio genu examinations for osteoarthritis cases.